Tongue coating removal: comparison of the efficiency of three techniques - Luciana Sassa Marocchio; Maurício Duarte da Conceição; Olinda Tárzia (Faculdade São Leopoldo Mandic, 2009)
Objective: Compare the efficiency of three techniques for tongue cleaning, by comparison of the amount of tongue coating removed by each technique. Methods: Tongue cleaning was performed using an Oral B 30 (Procter&Gamble, São Paulo, Brasil) toothbrush; a Saude Bucal (Odomed, São Paulo, Brasil) tongue scraper, and a new tongue cleaning technique, consisting of a tongue cleaner with bristles and a scraping edge and a Halitus® (Halitus, Campinas, Brasil) tongue cleaning spray solution. The study design used 15 healthy volunteers who were submitted to each of the tongue cleaning techniques, once every 21 days. The volunteers were instructed to abstain from any procedure to clean their tongues, for 48 hours before the application of each technique. At each scheduled time, a dental professional performed a single standardized tongue cleaning procedure using one of the cleaning methods, and inserted the removed tongue coating into a test tube. Results: The results were obtained by weighing the tube test with tongue coating after the cleaning procedure (final weight) deducting the weight of the empty tube test (initial weight). The findings showed that the new tongue cleaning technique (combination of a tongue cleaner with brush and scraper plus a tongue cleaning spray solution) was statistically superior in removing tongue coating when compared with the tongue scraper or toothbrush, probably due to the technique and materials used. Conclusion: The tongue cleaning procedure, when performed within a specific technique, associated with products that improve the cleaning action, makes possible to reach better results, allowing the removal of more tongue coating.